IMPLEMENTASI BUKU SYAMIL PADA PEMBELAJARAN BAHASA ARAB DI UIN WALISONGO SEMARANG - Iqbal Ahsanul Aula Iqbal; Nazih Sadatul Kahfi; Azex Azka Nufus (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2024)
Arabic has a strategic role because it supports the understanding of Islamic teachings. Therefore, learning Arabic in Islamic universities is very important because it is a scientific scientific transformation of classical, medieval, and modern intellectual treasures. This research is a qualitative research with a case study approach, in which the subjects are students majoring in Chemistry, Faculty of Chemistry, Faculty of Islamic Studies. where the subjects are students majoring in Chemistry at the Faculty of Science and Technology of UIN Walisongo Semarang, and the object is the Arabic learning process in the classroom as well as the students' achievement during the learning process. learning process in the classroom as well as student achievement during learning. The result of the research The results showed that the use of Syamila books in Arabic language learning is very appropriate because it covers four skills: listening, speaking, reading, and writing.